2021
DOI: 10.1097/mcp.0000000000000806
|View full text |Cite
|
Sign up to set email alerts
|

Sarcoidosis and maligancy: the chicken and the egg?

Abstract: Purpose of reviewThere is a complex interaction between sarcoidosis and malignancy. Since tumors can elicit a granulomatous reaction, the presence of granulomas alone is insufficient to diagnose sarcoidosis in a patient with cancer. In addition, check point inhibitors can also lead to a granulomatous reaction which can be misdiagnosed as sarcoidosis. These issues need to be considered when exploring the relationship between sarcoidosis and malignancy. Despite these limitations, a growing amount of evidence sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 46 publications
0
5
1
Order By: Relevance
“…52 Moreover, it remains unclear if sarcoidosis precedes or follows NHL, as several observational studies reported occurrence of sarcoidosis among NHL patients after treatment of NHL or concomitant occurrence of two diseases. 1922…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…52 Moreover, it remains unclear if sarcoidosis precedes or follows NHL, as several observational studies reported occurrence of sarcoidosis among NHL patients after treatment of NHL or concomitant occurrence of two diseases. 1922…”
Section: Discussionmentioning
confidence: 99%
“…Although we also observed a negative association between genetically predicted susceptibility to sarcoidosis and NHL, the association was no longer significant after accounting for multiple testing. While no previous epidemiologic studies have reported statistically significant negative associations for either T1D or sarcoidosis with NHL, 8,9,13,22,51 it has been suggested that the pathways involved in autoimmune disease and cancer development may work in opposite directions. 52 Moreover, it remains unclear if sarcoidosis precedes or follows NHL, as several observational studies reported occurrence of sarcoidosis among NHL patients after treatment of NHL or concomitant occurrence of two diseases.…”
Section: Context Of Primary Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…Yet it is still not very clear the cut off criteria for the differentiation of the sarcoidosis and the sarcoid-like reactions in patients with malignancy which might be a subject of changes in evaluation of the entities in the future. Bonifazi et al proposed a diagnostic work-up for cancer patients with an identification of granuloma on biopsy and stated that elevated ACE, granulomas in areas remote from cancer, previous diagnosis of sarcoidosis, atypical involvement for cancer ( ocular, skin, parenchymal lung disease and cardiac) and hypercalcemia with high vitamin D1,25 and low vitamin D25 and PTH are features that favor sarcoidosis rather than a relapse of the malignancy [30].…”
Section: Discussionmentioning
confidence: 99%
“…Other conditions, such as infectious disorders and cancer, have also been shown to be associated with a granulomatous reaction, mimicking sarcoidosis. In addition, certain drugs may also induce OPEN ACCESS EDITED BY sarcoid-like reactions indistinguishable from sarcoidosis (Bonifazi et al, 2015;Bonifazi et al, 2021;Tana et al, 2022).…”
Section: Introductionmentioning
confidence: 99%